Prevalence of untreated dental caries in Latin American children in the Spanish child protection system - Gonzalo Oliván-Gonzalvo (Emergency Department of Hospital San Pedro (Logroño, Spain), 2020)
Introduction and objective: The study aimed to investigate the prevalence of untreated dental caries in Latin American immigrant children who enter into the child protection system in Aragon, Spain. We analyze if these are related to demographic factors, body mass index, or vulnerability circumstances. Methods: Cross-sectional observational study. We analyze the social and health records of every child between the age of 6 and 17 that required residential care in the period between 2000 and 2019. The Social Services Institute of Aragon who compiled their records and directed the protection measures assessed their vulnerability conditions. A standard anthropometric and oral evaluation by healthcare professionals, together with the recollection of their demographic data, was carried out as these children accessed the welfare system. Results: Two hundred and thirty-one children (55.8% female) with an average age (SD) of 13.6 (3.8) years were evaluated. The prevalence of untreated dental caries was 16.5%. These were associated to the age group 6-13 years-old (p<0.001), the second-generation (p=0.004) and the temporary or permanent parental inability to provide child welfare (p=0.009) due to death, incarceration, physical illness, mental illness, drug addiction, or causes of a similar nature, together with the absence of relatives taking care of the child. The prevalence of overweight and obesity was 32% and do not exhibited association with the presence of untreated dental caries. Conclusion: We observe either that, besides cariogenic dietary habits acquired in their native community or their foster one, socio-family vulnerability and deprivation play an essential role in the high prevalence of untreated dental caries.